FIGHT AGAINST SEXUAL ABUSE AND ONLINE EXPLOITATION OF CHILDREN – KEY PRIORITY AT THE EUROPEAN UNION LEVEL - TOLBARU, Carmina-Elena (International Journal of Legal and Social Order, 2022)
We are experiencing a period full of physical and virtual uncertainty and insecurity, the Covid-19 period being a milestone regarding the increase of the phenomenon of sexual abuse and online exploitation of children. The wide accessibility of technology creates the opportunity for offenders to commit such crimes on children. Protection of children against any form of violence or abuse is a key priority at the European Union level, aiming at fighting the online and offline abuse on children, including production and diffusion of materials showing abuses on children, such as online sexual exploitation of children. In this regard, the European Union efforts aim at creating a specific legal framework in order to make easier for the Member States to detect and report the cases of online sexual abuse, to prevent such situations, and to support the victims. Thus, the Commission wants to clarify the role that the online service providers should have in order to protect the children. The main problem identified is the scarce reporting of such crimes, and therefore, the impossibility of identifying the victims.